Developing Public-Private Partnerships in Liberia - Kaplan, Zachary A.; Kyle, Peter; Shugart, Chris; Moody, Alan (World Bank, 2012)
The Government of Liberia is in the process of developing a new Poverty Reduction Strategy (PRS) that is intended to determine its path toward middle-income status. One central aspect of the strategy is likely to be a stronger focus on inclusive growth. This will mean that higher priority will be placed on growing the local private sector, and broadening the base of the economy. Public-private partnerships (PPPs) in infrastructure and services can be a key instrument for achieving these goals especially in an economy like Liberia. The analysis contained in this study identifies the steps toward establishing PPPs as both a policy instrument and method for deepening private sector investment in Liberia. Liberia's rich natural resource endowments have played a fundamental role in the way in which the economy has developed, and in the way in which Government manages private investment in extractive industries. The Government itself has a long history of entering into concession contracts with private investors and operators. Firestone rubber first signed a concession agreement in 1926, and re-signed their concession to last until 2041. More recently, the Government of Liberia has entered into several large natural resource and mining concession contracts that will see large sums of private sector capital invested onshore. This study is one element of a multi-faceted effort to support local private sector and financial sector development in Liberia. It takes into close account the Government's focus on job-creation, the post-conflict dynamics in the country, and Liberia's reliance on extractive industries as a primary source of revenue. The analysis also builds on previous economic sector work that has looked closely at how to stimulate private sector growth and investment, how to support small and medium-size enterprise (SME), and how to leverage existing private sector investment to generate deeper local markets and create new jobs.